Establishing the use of a safety attitudes questionnaire to assess the safety climate across a critical care network. (August 2018) - Thomas, Antony; Lomas, John-Paul
Aims: We aimed to measure the safety culture across a network of critical care units to compare units, track temporal changes and to present easy to interpret information back to staff. Methods: We provided adapted paper versions of the short ICU 'Safety attitude questionnaire' to 14 critical care units annually between 2015 and 2017. The responses were analysed to establish scores for individual safety domains. Feedback used colour conditional formatted tables to allow easy identification of high and low scores. Results: There was an inverse relation between median unit score and standardised mortality (rs  = 0.4). Rates of staff fatigue increased between 2016 and 2017 (two-point change on a 1–5 scale). Conclusions: A critical care network can usefully collect and feedback safety attitude questionnaires which show a relationship with patient outcome. Units should monitor overtime working.